FUNDAMENTAL ANALYSIS FOR DISCRIMINANT OF STOCK PRICE - Sopani, Cepiana; Kusmayadi, Dedy M.; Parlina, Nurhana Dhea (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2024)
The decline in stock prices indicates the company's condition. Profit is essential in knowing the company's condition as earnings per share and from all debts as Debt to equity ratio, which is a fundamental analysis. This study uses causal associative methods, secondary data derived, and the determination of the sample study using a purposive sampling technique, which obtained eight companies as samples. This study aims to determine the effect of earnings per Share (EPS) and Debt To Equity Ratio (DER) on stock prices in the coal mining sub-sector companies listed on the Indonesia Stock Exchange in 2017-2021. Data analysis techniques used are classical assumption testing, multiple linear regression analysis, coefficient of determination, hypothesis testing, and using SPSS Version 25. The value Debt To Equity Ratio (DER) has no significant adverse effect on stock prices and, based on the F test, simultaneously shows that earnings per Share (EPS) and the Debt to equity ratio (DER) simultaneously or simultaneously have a significant effect on stock prices. The results of the data analysis show that Earning Per Share (EPS) has a significant positive effect on stock prices.